2019
DOI: 10.3390/ijms20184482
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Dual Strands of miR-143 (miR-143-5p and miR-143-3p) and Their Target Oncogenes in the Molecular Pathogenesis of Lung Adenocarcinoma

Abstract: Our analyses of tumor-suppressive microRNAs (miRNAs) and their target oncogenes have identified novel molecular networks in lung adenocarcinoma (LUAD). Moreover, our recent studies revealed that some passenger strands of miRNAs contribute to cancer cell malignant transformation. Downregulation of both strands of the miR-143 duplex was observed in LUAD clinical specimens. Ectopic expression of these miRNAs suppressed malignant phenotypes in cancer cells, suggesting that these miRNAs have tumor-suppressive activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 49 publications
1
69
0
Order By: Relevance
“…RAD51 is also highly expressed in many cancers (Lee et al, 2019;Zhang W. et al, 2019) and has been identified as a radiosensitive target for many cancers (Chen et al, 2012). Sanada et al (2019) evaluated the miR-143-5p molecular network in LUAD using whole-genome sequencing combined with miRNA database analysis and identified 11 prognostic target genes, including RAD51. Another study showed that the abnormal expression of other genes, such as cancer testis antigen (CTA), can also promote RAD51 filament formation and simultaneously enhance the sensitivity to DNA damaging agents (Nichols et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…RAD51 is also highly expressed in many cancers (Lee et al, 2019;Zhang W. et al, 2019) and has been identified as a radiosensitive target for many cancers (Chen et al, 2012). Sanada et al (2019) evaluated the miR-143-5p molecular network in LUAD using whole-genome sequencing combined with miRNA database analysis and identified 11 prognostic target genes, including RAD51. Another study showed that the abnormal expression of other genes, such as cancer testis antigen (CTA), can also promote RAD51 filament formation and simultaneously enhance the sensitivity to DNA damaging agents (Nichols et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, it is highly expressed in mesenchymal cells, such as fibroblasts and smooth muscle cells 15 . Despite the existence of a few reports regarding the suppressive function of MIR143‐5p, knowledge on the function of MIR143‐5p remains limited 16 …”
Section: Functions Of Mir143mentioning
confidence: 99%
“…24 MiR-143-5p was involved in lung adenocarcinoma pathogenesis via interacting with its target genes. 25 Moreover, miR-143-3p also inhibited expression of Wnt5a, LRP5, Axin2, and β-catenin. 26 With respect to PRDX5, it belongs to the family of antioxidant enzymes with six identified isoforms.…”
Section: Discussionmentioning
confidence: 97%